Pre-activation of SBA-15 intermediate barriers with Pd nuclei to increase thermal and mechanical resistances of pore-plated Pd-membranes. (3rd June 2021) - Sanz-Villanueva, D.; Alique, D.; Vizcaíno, A.J.; Sanz, R.; Calles, J.A.
Abstract: Thermal and mechanical resistances of palladium composite membranes prepared by Electroless Pore-Plating (ELP-PP) and containing SBA-15 as intermediate layer were improved by doping the silica material with Pd nuclei before its incorporation on the composite membrane. Textural properties of synthesized SBA-15 materials (both raw and doped ones) were analyzed by XRD, N2 adsorption-desorption at 77 K and TEM, while the main properties of the composite membrane were determined by SEM and gravimetric analyses. Moreover, membrane permeation tests were also carried out with pure gases, hydrogen and nitrogen, and binary mixtures of them at temperature of 400 °C and pressure driving forces in the range of 0.5–2.5 bar. The use of bare SBA-15 intermediate layer leads to the appearance of cracks on the Pd layer during permeation experiments at high temperature. In contrast, the use of Pd-doped SBA-15 particles avoids this problem, thus improving both thermal and mechanical resistances of the composite ELP-PP Pd-membrane. Following this preparation method, an estimated Pd thickness of 7.1 μm was obtained, reaching a hydrogen permeance of 3.81·10 −4 mol s −1 m −2 Pa −0.5 and ensuring an ideal H2 /N2 separation factor higher than 2550 at 400 °C. Graphical abstract: Image 1 Highlights: Doping SBA-15 with Pd nuclei before its incorporation improves membrane properties. Pd thickness of 7.1 μm was reached, saving around 68% metal compared to raw SBA-15. H2 permeance 3.81·10 −4 mol/s m 2 Pa 0.5 and αH2/N2 ≥2550 were obtained. Mechanical and thermal resistances are ensured at 400 °C during all experiments.